Comment Roger de Barneville est-il mort ? Sur les rapports entre les chroniques latines de la première croisade - Edoardo D’Angelo (Tabularia)
Studies of the relationships among the Latin chronicles on the first Crusade, particularly looking to the Hystoria de via et recuperatione Antiochiae atque Ierusolymarum, analysing the different accounts of Roger of Barneville’s death fighting against Turks. The analysis of this episode demonstrates that the so called Gesta Francorum and Petrus Tudebodus derive from an original account, now lost.